Job satisfaction among nurses in general hospitals in Chengde City, China - Liu, Jing Hua (2015)
Introduction: Hospitals in China continuously witnesses the challenge of nursing shortage. Job satisfaction is strongly related to the retention of skilled nurses. Although many studies regarding to nurses’ job satisfaction have been reported in China, there is a paucity of publications on hospital’s level impacting on nurses’ job satisfaction. Objective: The aim of this study were to determine nurses’ job satisfaction in general hospitals and to compare nurses’ job satisfaction between second and third level hospital in Chengde City, Hebei Province, China. Methods: A cross-sectional study was conducted among 490 nurses in general hospitals. Data collection used a self-administered questionnaire. Job satisfaction was measured using Chinese Nurses Job Satisfaction Scale (CNJSS). Data were analyzed using IBM SPSS version 20.0. Descriptive statistics used Mean and Standard deviation. Comparison of overall job satisfaction score between two groups used t-test and one-way ANOVA for more than two groups. One-way MANOVA was conducted to compare the mean scores of job satisfaction sub-scales between second and third level hospital. The level of significance was set at α = 0.05. Results: The response rate was 91.4%. The mean (M) ± standard deviation (SD) overall job satisfaction in general hospitals was 2.86 ± 0.31. Nurses rated co-worker (3.94 ± 0.45) as the most satisfied facet and work itself (2.11± 0.47) as the most dissatisfied facet among the eight job satisfaction sub-scales. In terms of the comparisons of overall job satisfaction in general hospitals, significant differences were found between gender (P<0.001), age group (P<0.001), educational background (P<0.001) and hospital’s level (P<0.001). Nurses’ overall job satisfaction in second-level hospital was significantly higher than those in third-level hospital (P < 0.001). Further analyses on the comparisons of eight job satisfaction sub-scales between second and third level hospital showed that nurses in second-level hospital were more satisfied with co-worker (P <0.001), family work balance (P<0.001) and praise/recognition (P<0.001), while less satisfied with pay than nurses in third-level hospital (P<0.001). Conclusion: Nurses in Chengde City were most satisfied with co-worker and most dissatisfied with work itself. In second-level hospital, nurses were more satisfied with coworker, family-work balance and praise/recognition, while less satisfied with pay than those in third-level hospital.